Artificial Intelligence in the Social Science Area: Systematic Literature Review in Web of Science and Scopus - Forteza Martínez, Aurora; Alonso López, Nadia (Revista Trípodos, 2024)
The evolution of technology is giving rise to new scenarios in communication, information access, and social relations. Particularly, artificial intelligence has a great impact on the current media ecosystem, including social, academic, communicative, health aspects, and interpersonal relationships. This research aims to study how artificial intelligence is reflected in the scientific production in the most relevant publications in Social Sciences. To this end, a systematic review of the scientific literature published in Spanish on the Web of Science and Scopus databases spanning from 2018 to the first three quarters of 2023 was carried out, following the standards of PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). From an initial sample of 159 articles, 109 were analysed after applying the inclusion and exclusion criteria. Results show that 2022 was the most productive year, with Spain having the highest number of publications. Furthermore, most of the research was published on Scopus and in the field of Law, with a predominance of qualitative methodology. The key themes were the benefits of implenting artificial intelligence (AI) and its dangers and threats.
Keywords: artificial intelligence; social sciences; systematic review; Web of Science; Scopus